Potential of condensate as a water source from air conditioning systems: A thermodynamic analysis - Koorosh Goudarzi (Journal of Applied Research in Water and Wastewater)
A considerable amount of water condensate produced through the cooling coils of air conditioning systems is usually directed to municipal sewage systems and wasted along with the energy it contains. This energy can instead be utilized to increase the efficiency of air conditioning systems and refrigeration systems in cold storage facilities, save energy consumption, reduce the carbon footprint, and also meet some of the water consumption needs. Since the choice of how to use condensate energy depends on its potential, i.e., the amount of collected water, this thermodynamics study estimates the amount of collected water and investigates the effects of various parameters such as ambient temperature, relative humidity (RH), coil temperature, etc., on the amount of water produced. The research results indicate that RH and air flow rate over the cooling coil have the greatest impact on the amount of water produced.